EXPLAINING CHILDREN ON YOUTUBE: THE CASE OF INDONESIAN SUBSCRIBER BEHAVIORAL INTENTION ON KIDZ YOUTUBE CHANNEL : Kajian Anak pada YouTube: Kasus Minat Subscriber Indonesia di Channel Youtube Kidz - Simanjuntak, Megawati; Putri, Marietta Krisnaya Nandika; Yuliati, Lilik Noor; Muflikhati, Istiqlaliyah; Retnaningsih, Retnaningsih; Johan, Irni Rahmayani (Jurnal Ilmu Keluarga dan Konsumen, 2023)
Understanding children’s behavior and intentions to subscribe to YouTube channels are important for production companies and parents. This study analyzed factors influencing children’s behavioral intention to subscribe to YouTube channels using UTAUT 2 model and SEM-PLS analysis. The samples were 100 kids aged 7 to 12 who live in the Greater Jakarta area. Data were collected through an online questionnaire. The results showed that habit and social influence significantly influenced children’s behavioral intention to use Kidz YouTube Channel. Children’s behavioral intention to use Kidz YouTube Channel significantly influenced children’s usage behavior. Moreover, children’s usage behavior significantly influenced their intention to subscribe to Kidz’s YouTube Channel. The study indicated that children’s decision to subscribe to YouTube channels was simple and relied on their habits and social influence. Therefore, parents need to supervise children’s activities on YouTube. Meanwhile, the content creator company could optimize a routine schedule for uploading a new video based on selected themes and also needs to increase parents’ awareness of the safety of their program.